1988
DOI: 10.1007/bf01655858
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subtotal thyroidectomy on Graves' ophthalmopathy

Abstract: Nineteen unselected patients undergoing subtotal thyroidectomy (STT) for Graves' disease were submitted to thorough ophthalmologic assessment before and after (mean, 10 mo) thyroid surgery. All clinical examinations were performed by the same observer and findings were scored according to the American Thyroid Association (“NOSPECS”) classification. Orbital computed tomography (CT) scans were performed in all patients prior to surgery and again at follow‐up if the initial scan was abnormal or if there was evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In the latter group, the ablation of residual thyroid tissue was associated with a significant improvement of eye manifestations. A beneficial effect of total thyroid ablation (surgery, radioiodine, or both) on the course of ophthalmopathy has been confirmed by some (56)(57)(58) but not all authors (38,(59)(60)(61), even though a tendency toward improvement more often followed ablative therapy with thyroid surgery than with radioiodine ( One of the main problems in evaluating the role of thyroid ablation on the course of ophthalmopathy is the difficulty of defining ablation. In fact, even in patients developing severe hypothyroidism following total thyroidectomy or radioiodine administration, residual thyroid tissue frequently can be demonstrated by thyroid scan.…”
Section: Thyroidectomymentioning
confidence: 92%
See 1 more Smart Citation
“…In the latter group, the ablation of residual thyroid tissue was associated with a significant improvement of eye manifestations. A beneficial effect of total thyroid ablation (surgery, radioiodine, or both) on the course of ophthalmopathy has been confirmed by some (56)(57)(58) but not all authors (38,(59)(60)(61), even though a tendency toward improvement more often followed ablative therapy with thyroid surgery than with radioiodine ( One of the main problems in evaluating the role of thyroid ablation on the course of ophthalmopathy is the difficulty of defining ablation. In fact, even in patients developing severe hypothyroidism following total thyroidectomy or radioiodine administration, residual thyroid tissue frequently can be demonstrated by thyroid scan.…”
Section: Thyroidectomymentioning
confidence: 92%
“…Ablation of thyroid tissue is not a standard procedure for treating Graves' hyperthyroidism, and subtotal thyroidectomy generally is reserved only for a minority of patients (those with large goiters or with relapsing hyperthyroidism at a young age). Several studies (30,36,52,59,63) have tried to ascertain whether, as suggested by Catz and Perzik (55), subtotal thyroidectomy may be followed by a worsening of ophthalmopathy. As indicated in Table 3, it is difficult to draw a definite conclusion, and no study has confirmed the constant worsening observed by Catz and Perzik (55).…”
Section: Thyroidectomymentioning
confidence: 99%
“…For those with relapsed GD after an adequate course of ATD, the decision for either RAI or thyroidectomy mostly depends on the presence of absolute or relative surgical indication. Thyroidectomy has gained an increasing role over RAI in relapsed GD as it offers more rapid and lasting control of the hyperthyroidism, and for those with preexisting GO, it could also possibly reverse a certain degree of proptosis, eyelid width, and diplopia [7, 911]. In contrast to previous studies that evaluated the effect of thyroidectomy on GO, the aim of the present study was to evaluate whether GO, which remains a relative surgical indication, would affect surgical outcomes in GD.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of serum levels of these antibodies after treatment with oral anti-thyroid drugs, radioactive iodine or surgical intervention seems to be an important prognostic factor of hyperthyroidism recurrence or progression of orbitopathy (14,15). On the other hand, decreased levels of these antibodies are associated with successive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It may be connected with various symptoms from only mild discomfort even up to serious damage, which may result in vision loss. Many studies comparing the results of radioactive iodine vs. surgical treatment on progressive orbitopathy showed that better long-term results were achieved following surgery (9,11,14).…”
Section: Discussionmentioning
confidence: 99%